Chromosome level assembly reveals a unique immune gene organization and signatures of evolution in the common pheasant. (2nd December 2020) - He, Chuan; Zhao, Lele; Xiao, Lu; Xu, Ke; Ding, Jinmei; Zhou, Hao; Zheng, Yuming; Han, Chengxiao; Akinyemi, Fisayo; Luo, Huaixi; Yang, Lingyu; Luo, Lingxiao; et al.
Abstract: The common pheasant Phasianus colchicus, belonging to the order Galliformes and family Phasianidae, is the most widespread species. Despite a long history of captivity, the domestication of this bird is still at a preliminary stage. Recently, the demand for accelerating its transformation to poultry for meat and egg production has been increasing. In this study, we assembled high quality, chromosome scale genome of the common pheasant by using PacBio long reads, next‐generation short reads, and Hi‐C technology. The primary assembly has contig N50 size of 1.33 Mb and scaffold N50 size of 59.46 Mb, with a total size of 0.99 Gb, resolving most macrochromosomes into single scaffolds. A total of 23, 058 genes and 10.71 Mb interspersed repeats were identified, constituting 30.31% and 10.71% of the common pheasant genome, respectively. Our phylogenetic analysis revealed that the common pheasant shared common ancestors with turkey about 24.7–34.5 million years ago (Ma). Rapidly evolved gene families, as well as branch‐specific positively selected genes, indicate that calcium‐related genes are potentially related to the adaptive and evolutionary change of the common pheasant. Interestingly, we found that the common pheasant has a unique major histocompatibility complex B locus (MHC‐B) structure: three major inversions occurred in the sequence compared with chicken MHC‐B. Furthermore, we detected signals of selection in five breeds of domestic common pheasant, several of which are production‐oriented.